The Concept of the Trust (al-Amaanah) and Its Implications in the Lightof the Holy Quran | مفهوم الأمانة ودلالاتها في ضوء القرآن الكريم - Ahmaddin Ahmad Tohar (Al-Zahra : Journal for Islamic and Arabic Studies, 2015)
This paper discusses the concept of al-amanah (the trust) in the Quran. Through this study appears that the word amanah mentioned in the Quran in the singular and plural. In scope, amanah consists of: the trust of the human with his God, and fulfill the mandate of God rights.